Strengthening the content of NDCs to better reflect farmer interests - Chevallier, Romy; Chesterman, Sabrina (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
While all countries in SADC have included agriculture in their 2015 NDCs, the levels of ambition and detail on agricultural and farming priorities vary. Countries can use the revision process to enhance the content and substance of their NDCs, as well as to improve the means of implementation. Farmers need to proactively engage in the content of their revised NDCs so ensure their interests are reflected.